2015
DOI: 10.3892/etm.2015.2537
|View full text |Cite
|
Sign up to set email alerts
|

Association between hepatitis B virus infection and diabetes mellitus: A meta-analysis

Abstract: Abstract. Hepatitis B virus (HBV) infection has been shown by certain studies to be associated with diabetes mellitus (DM); however, the results of these studies were controversial. For that reason, a meta-analysis of the literature was performed in order to determine the association between HBV infection and the prevalence of DM more accurately. The PubMed, Embase, Chinese National Knowledge Infrastructure and Wan Fang databases, as well as the Chinese Science and Technology Journal Database, were searched fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 27 publications
4
43
0
Order By: Relevance
“…The main reasons behind hepatocellular injury in FLD are elevated intracellular fatty acids, oxidative stress, and mitochondrial dysfunction. Another potential factor may be insulin-related disorders such as insulin resistance (25). In line with our findings, a study on 214 patients with FLD showed that 89% of them had a BMI of more than 25 (26).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The main reasons behind hepatocellular injury in FLD are elevated intracellular fatty acids, oxidative stress, and mitochondrial dysfunction. Another potential factor may be insulin-related disorders such as insulin resistance (25). In line with our findings, a study on 214 patients with FLD showed that 89% of them had a BMI of more than 25 (26).…”
Section: Discussionsupporting
confidence: 73%
“…Hyperinsulinemia promotes the replication of hepatitis B and C viruses. Moreover, diabetes mellitus suppresses the immune system, increases serum levels of free fatty acids, and increases the incidence and the severity of steatosis, steatohepatitis, and liver fibrosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al. (2014) performed a meta‐analysis that indicated that patients with HBV infection were at a higher risk of developing DM when compared with patients without HBV infection . However, they did not correctly differentiate between the HBV infection phases for many of the original articles.…”
Section: Discussionmentioning
confidence: 99%
“…In the Asia-Pacific area, the rate of DM in patients with HBV was higher than in patients uninfected with HBV [odds ratio (OR) 1.67] [16]. Hepatitis B surface (HBsAg) carriers had a three times higher rate (32.9%) of developing gestational diabetes compared with the regular population [17].…”
Section: Dm and Hepatitis Bmentioning
confidence: 99%